Selenium biofortification improves nutraceutical quality and antioxidant capacity of lettuce (Lactuca sativa L.) - Buendía-García, Alain; Lozano-Cavazos, Carlos Javier; Rodríguez-Ortiz , Juan Carlos; Carballo-Méndez, Fernando de Jesús; Moreno-Reséndez, Alejandro; Sariñana-Navarrete, María de los Ángeles; Preciado-Rangel, Pablo (Ecosistemas y Recursos Agropecuarios, 2021)
Selenium (Se) is an essential micronutrient for humans and its deficiency affects 15% of the world’s  population. Agronomic biofortification improves the biosynthesis of bioactive compounds and promotes their bioaccumulation. In the present  work, the effect of foliar application of Se on yield,  biosynthesis of bioactive compounds and accumulation in lettuce (Lactuca sativa L.) cv “Parris  Island cos”. was evaluated. Five treatments were  used: 0, 10, 20, 40 and 60 μ M L-1. Biofortification with the biosynthesis of phytochemical compounds  and their concentration in lettuce leaves was  positively modified, without affecting the yield. Se  foliar spraying is an alternative to increase the  biosynthesis of phytochemical compounds and  increase the concentration of this element in lettuce  with the possibility of improving public  health with its consumption.